2017
DOI: 10.1371/journal.pntd.0005300
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Tc52 or its amino terminal domain adjuvanted with c-di-AMP induces Th17+Th1 specific immune responses and confers protection against Trypanosoma cruzi

Abstract: The development of new adjuvants enables fine modulation of the elicited immune responses. Ideally, the use of one or more adjuvants should result in the induction of a protective immune response against the specific pathogen. We have evaluated the immune response and protection against Trypanosoma cruzi infection in mice vaccinated with recombinant Tc52 or its N- and C-terminal domains (NTc52 and CTc52) adjuvanted either with the STING (Stimulator of Interferon Genes) agonist cyclic di-AMP (c-di-AMP), a pegyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…Very promising results were obtained when c-di-AMP was assessed as adjuvant in different prototypes of mucosal vaccines against different viruses and bacteria ( Sanchez et al, 2014 ; Landi et al, 2017 ; Schulze et al, 2017 ). Particularly, this adjuvant has also been used in previous studies for the design and experimental assessment of subunit vaccines formulations against T. cruzi ( Matos et al, 2017 ; Sanchez Alberti et al, 2017 ). In these studies, recombinant T. cruzi antigens were formulated together with c-di-AMP and were administered nasally, obtaining an immune response that allowed protection after the challenge with the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very promising results were obtained when c-di-AMP was assessed as adjuvant in different prototypes of mucosal vaccines against different viruses and bacteria ( Sanchez et al, 2014 ; Landi et al, 2017 ; Schulze et al, 2017 ). Particularly, this adjuvant has also been used in previous studies for the design and experimental assessment of subunit vaccines formulations against T. cruzi ( Matos et al, 2017 ; Sanchez Alberti et al, 2017 ). In these studies, recombinant T. cruzi antigens were formulated together with c-di-AMP and were administered nasally, obtaining an immune response that allowed protection after the challenge with the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, recombinant T. cruzi antigens were formulated together with c-di-AMP and were administered nasally, obtaining an immune response that allowed protection after the challenge with the parasite. Moreover, using the Tc52 T. cruzi antigen, Matos and colleagues described a better adjuvant ability of c-di-AMP in comparison with CpG, one of the most potent adjuvants for the development of vaccines against intracellular microorganisms ( Matos et al, 2017 ). Reinforcing these data, our results also show that an engineered L. lactis that overexpresses c-di-AMP and a TS fragment could result in an effective vaccine for Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, co-cultures of T. cruzi infected macrophages with live neutrophils isolated from BALB/c and C57BL/6 resulted also in increased and decreased parasite replication, respectively (Luna-Gomes et al, 2014 ), indicating the importance of the mouse genetic background in T. cruzi infection. In addition, anti osteopontin antibody treatment in C57BL/6 infected with the Y strain (Santamaría and Corral, 2013 ) and T. cruzi TC52 antigen immunized C3H/HeN mice infected with the RA strain (Matos et al, 2017 ), induced a high Th1 response that protected mice from infection. However, it is important to point out that the development of severe CCC in humans is also thought to be due to a Th1-specific immune response (Gomes et al, 2003 ), thus some regulation seems to be needed to avoid disease progression.…”
Section: Cd4+ T Cell Subsetsmentioning
confidence: 99%
“…Recently, several reports using mice with C57BL/6 background infected with the Tulahuén strain showed that Th17 high levels conferred protection against infection using Il-23 inhibitory BATF2 (Kitada et al, 2017 ), regulatory EBI3 (Böhme et al, 2016 ), IL-17A (Miyazaki et al, 2010 ) and IL-17RA (Tosello Boari et al, 2012 ) deficient mice. On the other hand, immunization of C3H/HeN mice with TC52, a T. cruzi protein with glutathione transferase activity and a vaccine candidate, conferred Th17 specific protection against infection with the RA strain (Matos et al, 2017 ). Similarly, adoptive transfer of BALB/c parasite transialidase (TS) specific Th17 cells into RAG mice (lacking B and T cells) conferred higher protection than TS specific Th1 cells against infection with the Tulahuén strain (Cai et al, 2016 ).…”
Section: Cd4+ T Cell Subsetsmentioning
confidence: 99%
“…However, priming cell-mediated immunity (CMI) through the employment of subunit vaccines models is challenging (19). We have recently reported the efficacy of the STING agonist, 3 ′ 5 ′ -c-di-AMP (CDA) for priming pathogenspecific immune responses where Th1/Th17 balanced immunity proved to be protective against this protozoan parasite (10,20).…”
Section: Introductionmentioning
confidence: 99%